STRATEGIC HUMAN RESOURCE MANAGEMENT IN THE DIGITAL ERA: ALIGNING TALENT WITH ORGANIZATIONAL GOALS - Yudi Kurniadi; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The digital era has transformed the role of human resource management (HRM) from a primarily administrative function to a strategic driver of organizational success. This study examines how strategic human resource management (SHRM) practices align talent with organizational goals in digital contexts. Using a narrative review methodology, relevant literature on SHRM, digital transformation, and talent alignment was analyzed to identify key trends, challenges, and best practices. Findings indicate that the adoption of digital tools, including artificial intelligence, HR analytics, and digital learning platforms, enables organizations to optimize recruitment, performance management, and workforce planning. These tools facilitate data-driven decision-making, enhance employee engagement, and improve alignment between individual competencies and strategic objectives. However, challenges such as resistance to change, skill gaps, and fragmented HR systems remain significant barriers to effective implementation. The study highlights that organizations integrating digital technologies with SHRM frameworks achieve higher productivity, better talent utilization, and stronger competitive advantage. Implications for HR managers include investing in digital solutions, strategic workforce planning, and continuous feedback systems to enhance talent alignment. The review contributes to both theory and practice by illustrating how SHRM in digital environments can serve as a strategic enabler of organizational performance.